2020
DOI: 10.1145/3427931
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subjective Methods for Quality Assessment of 3D Graphics in Virtual Reality

Abstract: Numerous methodologies for subjective quality assessment exist in the field of image processing. In particular, the Absolute Category Rating with Hidden Reference (ACR-HR), the Double Stimulus Impairment Scale (DSIS), and the Subjective Assessment Methodology for Video Quality (SAMVIQ) are considered three of the most prominent methods for assessing the visual quality of 2D images and videos. Are these methods valid/accurate to evaluate the perceived quality of 3D graphics data? Is the presence of an explicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…A crowdsourcing (CS) experiment has been carried out in which subjects were recruited to assess the quality of an animated 3D graphics dataset. Since our goal is to compare the results of this experiment to previously collected Lab results [14], we replicated the lab experiment as much as possible, using the same instructions, dataset and subjective evaluation methodology. This section provides details on the CS experiment.…”
Section: Crowdsourcing Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…A crowdsourcing (CS) experiment has been carried out in which subjects were recruited to assess the quality of an animated 3D graphics dataset. Since our goal is to compare the results of this experiment to previously collected Lab results [14], we replicated the lab experiment as much as possible, using the same instructions, dataset and subjective evaluation methodology. This section provides details on the CS experiment.…”
Section: Crowdsourcing Experimentsmentioning
confidence: 99%
“…The 3D graphic stimuli used in this study were previously used in the laboratory based subjective experiment, reported in [14]. This dataset contains 80 animated meshes with diffuse color information.…”
Section: A Datasetmentioning
confidence: 99%
See 3 more Smart Citations